Understanding Parents’ School Selection Preferences: A Case Study of Sekolah Dasar and Madrasah Ibtidaiyah in Tulungagung - Sukmawati, Anis (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2025)
This study analyses parent’s perceptions in choosing Public Primary School (SD Negeri) and Islamic Primary School (MI) in Bandung sub-district, Tulungagung district. The decrease in the number of students at SDN and an increase at Islamic Primary School in recent years indicates a shift in community interest in educational institutions managed by the Ministry of Religious Affairs. Data were collected through interviews, observation, and documentation using descriptive qualitative methods. The results show that parents at SDN 1 Bandung prioritize academic achievement at an affordable cost, while parents at MI Al Azhaar Bandung prioritize religious and moral education, despite the higher costs, which adequate school facilities and services offset. Factors such as teacher competence, teaching quality, facilities, curriculum, student achievement, school environment, and tuition fees are key determinants in parent’s decisions. This research highlights the importance of adapting educational approaches to community expectations and local needs and how these factors influence parent’s school choices.